Predictors of students’ SQ3R in Learning Statistics During Distance Education: an Ordinal Logit Modeling - Casinillo, Leomarich F; Hungo, Melbert; Hermano, Rujube (Jurnal Pendidikan Indonesia, 2024)
Studying statistics during distance education is challenging due to limitations and communication problems. This has an impact on learning activities that could be more optimal. This research aims to analyze students' SQ3R level in learning statistics and determine its significant predictors. This type of research is quantitative research. The research design of this study is complex correlational research. The data collection method uses a questionnaire. Data analysis techniques use descriptive and inferential statistics. Secondary data from existing research studies were used and summarized using standard statistical metrics. In addition, ordinal regression analysis was used to determine the predictors of students' SQ3R level in statistics learning and was tested at a standard significance level. Findings reveal that students usually use the SQ3R method to learn statistics during online learning. The statistical model illustrates that students' ability to read and review statistics is shaped by the learning environment, teaching attitudes, physical and emotional health, and free time activities. The study suggests that to improve students' learning of statistics in distance education, educational institutions and professors should create a conducive learning environment, use strategic teaching methods, and emphasize the importance of harmonious study habits due to the SQ3R method.